A systematic comparison between 1‐D and 3‐D hemodynamics in compliant arterial models. (24th September 2013) - Xiao, Nan; Alastruey, Jordi; Alberto Figueroa, C.
SUMMARY We present a systematic comparison of computational hemodynamics in arteries between a one‐dimensional (1‐D) and a three‐dimensional (3‐D) formulation with deformable vessel walls. The simulations were performed using a series of idealized compliant arterial models representing the common carotid artery, thoracic aorta, aortic bifurcation, and full aorta from the arch to the iliac bifurcation. The formulations share identical inflow and outflow boundary conditions and have compatible material laws. We also present an iterative algorithm to select the parameters for the outflow boundary conditions by using the 1‐D theory to achieve a desired systolic and diastolic pressure at a particular vessel. This 1‐D/3‐D framework can be used to efficiently determine material and boundary condition parameters for 3‐D subject‐specific arterial models with deformable vessel walls. Finally, we explore the impact of different anatomical features and hemodynamic conditions on the numerical predictions. The results show good agreement between the two formulations, especially during the diastolic phase of the cycle. © 2013 The Authors. International Journal for Numerical Methods in Biomedical Engineering published by John Wiley & Sons, Ltd.